Эволюция кислого и среднего вулканизма в зеленокаменных поясах Украинского щита и Воронежского кристаллического массива - Артеменко, Г.В.; Самборская, И.А.; Вильковский, В.А.; Швайка, И.А. (Мінералогічний журнал, 2010)
Вулканиты кислого состава в зеленокаменных поясах курского типа, выделяемые в Приазовском и Курском гранулит-гнейсовых геоблоках, формировались в коровых магматических источниках. Андезиты для зеле нокаменных поясов этого типа не характерны. В зеленокаменных структурах приднепровского типа в Среднеприднепровском и Сумском блоках андезиты и кислые вулканические породы ранней дацит-андезит-толеитовой формации (3140 млн лет) и более поздних — риолит-дацитовой и риолит-сланцевой формаций (3100—3000 млн лет) по геохимическим характеристикам существенно различаются. Первые формировались главным образом в коровых (<40 км), а вторые — в более глубинных магматических источниках (>40 км). Полученные геохимические данные свидетельствуют о многообразии геодинамических обстановок кислого и среднего вулканизма в зеленокаменных поясах Украинского щита и Воронежского кристаллического массива. Вулканіти кислого складу в зеленокам’яних поясах курського типу, які виділяють у Приазовському та Курському грануліт-гнейсовому геоблоках, формувались у корових магматичних джерелах. Андезити для зеленокам’яних поясів цього типу не характерні. У зеленокам’яних структурах придніпровського типу в Середньопридніпровському та Сумському блоках андезити та кислі вулканічні породи ранньої дацит-андезиттолеїтової формації (3140 млн рр.) і більш пізніх — ріоліт-дацитової та ріоліт-сланцевої формацій (3100—3000 млн рр.) за геохімічними характеристиками істотно розрізняються. Перші утворились головним чином у корових (<40 км), а інші — у більш глибинних магматичних джерелах (>40 км). Отримані геохімічні дані свід чать про різноманіття геодинамічних обстановок кислого та середнього вулканізму в зеленокам’яних поясах Українського щита та Воронезького кристалічного масиву. The results of geochemical studies of volcanic rocks of intermediate and acid compositions in the greenstone belts of the Ukrainian Shield and Voronezh Crystalline Massif suggest that the evolutionary changes in their composition are associated with a change of geodynamical conditions of formation of these zones and the regional (lateral) differences in their composition are conditioned by different type and capacity of the foundation. Volcanic rocks of acid composition in the greenstone belts of the Kursk type allocated on the Peri-Azovian and Kursk granulite-gneiss geoblocks were formed in crustal magma sources and are significantly contaminated with crustal material. Andesites are not characteristic of the greenstone belts of this type. In greenstone structures of the Dnieper type on the Middle-Dnieper and Sumy blocks the andesites and acidic volcanic rocks of early dacite-andesite-tholeiitic formation (3140 Ma) and later — rhyolite-dacite and rhyolite-shale formations (3100—3000 Ma) are significantly different by geochemical characteristics. The former were mainly formed in the crust (<40 km), and the latter — in deeper magmatic sources (>40 km). Geochemical data evidence for the diversity of geodynamic environments of acid and intermediate volcanism in the greenstone belts of the Ukrainian Shield and Voronezh Crystalline Massif. Andesites and volcanic rocks of acid composition of Neoarchean-Paleoproterozoic age (Gulaypole suite of the Ukrainian Shield and Lebedin series of Voronezh Crystalline Massif are characterized by distinct crystal geochemical characteristics.